EDUKASI CARA BETERNAK AYAM DI DESA SERUAWAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Papilaya, Bercomien Juliet; Labetubun, Jusak; Sarfan, Riri; Rehatta, Lea Marylin (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Knowledge and skills among school children, particularly in raising native chickens as a source of animal protein, can foster motivation, diligence, entrepreneurship, and strong character, enabling them to contribute positively to their communities. Native chicken farming has great potential to meet family needs, especially children’s animal protein intake, while also providing additional household income. Animal protein is a vital nutrient for improving children’s nutritional status and serves as a long-term investment in health. The protein and fat found in chicken meat and eggs supply the energy children need for daily activities. The government’s long-standing program on the intensification of local chicken farming aims to increase poultry populations and meet the growing demand for animal protein. The potential of native chickens can be further developed by using better breeds, good management, quality feeding, and the use of locally materials. The general objective of this initiative is to improve native chicken production by identifying superior roosters and hens and utilizing agricultural waste effectively. Its specific objectives are to enhance knowledge of protein’s importance and develop practical skills in raising high-quality native chickens. The target group is school-aged youth, with success measured through increased interest and participation during training, discussions, and demonstration plots.